A process evaluation revealed that flexibility was key to delivering nutrition education to vulnerable tribal groups in India - Mockshell, Jonathan; Ritter, Thea; Garrett, James (SAGE Publications, 2025)
Background This study is a process evaluation of a nutrition education intervention that is part of a large-scale development program targeting vulnerable tribal groups in Odisha, India. Objective The objectives are to examine whether the intervention is operating as planned (implementation fidelity), investigate potential pathways to achieve greater impact, and provide recommendations on how to design nutrition education interventions in similar contexts. Methods A program impact pathway forms the basis of this process evaluation, tracing inputs, processes, outputs, outcomes, and impacts. The study's mixed-methods approach includes semistructured interviews, focus group discussions, and Process Net-Mapping. Narrative analysis was applied to examine the transcripts. Data were analyzed in the context of the program impact pathway. Results The intervention was not delivered as intended (low implementation fidelity). Flexibility was key in providing nutrition education to beneficiaries despite challenges, such as the inability to utilize behavior change communication, inadequate funding, and language and cultural barriers. Despite low fidelity, the qualitative results show that the intervention improved awareness of nutrition and health among beneficiaries. Conclusions Providing adequate resources for training frontline workers and beneficiaries is required for nutrition education programs to achieve their desired effectiveness and impact. Utilizing existing organizations, integration into production-based interventions, and incorporating easy-to-understand nutrition models, practical demonstrations, and videos would increase frontline worker and beneficiary engagement and understanding, leading to improved maternal and child nutritional and health outcomes.